Acute kidney injury and chronic kidney disease in Chile: Temporal trends in hospitalization rates from 2010 to 2019 - Luis Celis; Jenny Ruedlinger; Cinthya Leiva; Camilo G. Sotomayor; Roberto Jalil; Sandra Cortés (PLoS ONE, 2025)
Background Kidney diseases pose considerable challenges to health systems affecting millions of people worldwide. In Latin America there are limited epidemiological studies on these conditions. Objective This study aimed to describe the national age-adjusted hospitalization trends for acute kidney injury (AKI) and chronic kidney disease (CKD) in the Chilean population. Methods We conducted a retrospective study using a secondary data from hospitalized cases diagnosed with AKI and CKD in Chile, from 2010 to 2019. Age-adjusted hospitalization rates and JoinPoint regression analysis were performed. Results Between 2010 and 2019, 26,715 hospitalizations of patients diagnosed with AKI and 99,816 patients with CKD were recorded. Nationally, long-term trends in age-adjusted hospitalization rates for AKI increased by 9.1% annually (95% CI: 8.0 to 10.5), whereas CKD hospitalization rates declined by 4.35% (95% CI: −5.76 to −2.99) over the study period. Short-term trends in AKI hospitalization rates showed initial declines in Maule between 2010–2017 (−7.97%, 95% CI: −13.63 to −6.04) followed by increases from 2017 to 2019 (8.45%, 95% CI: −4.08 to 17.66), whereas Valparaíso (7.2%, 95% CI: 5.2 to 9.5) experienced steady growth. Although CKD rates generally declined, central regions such as O’Higgins and Maule showed increases between 2016–2019 (10.6%, 95% CI: 5.1 to 19.9) and 2017–2019 (8.5%, 95% CI: −4.1 to 17.7), respectively. Conclusion/Interpretation This study highlights AKI as a growing public health challenge nationwide, with increasing hospitalization rates. At the same time, CKD hospitalizations show a reduction, although regional disparities remain a concern. Efforts should focus on enhanced integral surveillance to address these trends effectively across the country.